Analisis Faktor-Faktor yang Mempengaruhi Kualitas Penyusunan Anggaran Sekolah Menengah Pertama: Studi Kualitatif di Medan - Nasution, Muwaffaq Fadhilsyah; Rahayu, Murni; Jannah, Nur Fadhilah; Tawarnate, Mahiri (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to analyze the factors that influence the quality of junior high school (SMP) budget preparation in Medan. Using a qualitative approach, this research involved in-depth interviews with 30 key informants from 10 junior high schools in Medan City. The research results identified 5 (five) main factors that influence the quality of budget preparation: (1) human resource competency, (2) government regulations and policies, (3) stakeholder participation, (4) use of information technology, and (5) culture school organization.